2021
DOI: 10.1016/j.phro.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric magnetic resonance imaging assessment of whole tumour heterogeneity for chemoradiotherapy response prediction in rectal cancer

Abstract: Background and purpose: Prediction of chemoradiotherapy response (CRT) in locally advanced rectal cancer would enable stratification of management. The purpose was to prospectively evaluate multi-parametric magnetic resonance imaging (MRI) assessment of tumour heterogeneity combining diffusion weighted imaging (DWI) and dynamic contrast enhanced (DCE) MRI for the prediction of CRT response in locally advanced rectal cancer. Materials and methods: Patients with Stage II or III rectal adenocarcinoma undergoing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Although ADC after CRT in this study was found to be useful in predicting pathological response to CRT [21], ADC was not useful for predicting DFS. A study by Bakke et al [17] of 27 patients also found that ADC before CRT was not able to predict DFS.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although ADC after CRT in this study was found to be useful in predicting pathological response to CRT [21], ADC was not useful for predicting DFS. A study by Bakke et al [17] of 27 patients also found that ADC before CRT was not able to predict DFS.…”
Section: Discussioncontrasting
confidence: 66%
“…The primary objective in this study, the correlation of MRI with CRT histopathological treatment response status, has been reported [20,21]. Our group found that ADC 75th and 90th quantile values after CRT were predictive of histopathological response status, with higher values predictive of response.…”
Section: Introductionmentioning
confidence: 80%
“…305,306,309 To better predict the disease progression, machine learning algorithms have been designed and applied to assist clinicians in analyzing patient information (some recent published papers are listed in Table 3). 190,193,230,[310][311][312][313][314][315][316][317][318][319][320][321] Recent disease risk prediction methods have mostly focused on head-and-neck cancer, 311,316 breast cancer, 190,193 rectal cancer, 312,313,315,319,321 brain cancer, 314,320 and liver disease, 317 For example, after stratifying glioblastoma patients were treated with chemoradiation therapy, 306 machine learning models were applied to patient OS time prediction. 305,306,309 Besides using mpMRI images, clinical profiles such as patient personal information, treatment factors, and genotypic-related features were combined for model training to improve the prediction accuracy.…”
Section: Patient Risk and Overall Survival Time Predictionmentioning
confidence: 99%
“…These permeability characteristics can be differentially visualised in parametric maps. As concurrent chemo-radiation is the standard treatment for locally advanced NPC patients, these parametric maps might be useful in monitoring angiogenic changes during chemo-radiation treatments [45] . Since we acquired the scans with an MR Simulator in which the patients were scanned in the same positions as their radiation treatment positions, the parametric maps had the same frame of reference as their radiation treatment plans.…”
Section: Discussionmentioning
confidence: 99%